Application Of Hooke's Law In Prosthetics - Gayibnazarov Rozimurod Bakhtiyarovich; Saipova Zamira Oybekovna (Genius Journals, 2024)
This paper examines methods for improving the production of prostheses by applying the laws of mechanics, in particular Hooke's laws.
Keywords: Hooke's law; prosthetics; nitinol; polyurethane elastomers